Weather - Rattini, Kristin Baird; National Geographic Society (U.S.) (Washington, D.C. : National Geographic Society, 2013)
Explores the causes of everyday weather phenomena, including how clouds form, why tornadoes twist, and how the sun helps life grow --
Look up at the sky -- What is weather? -- The sun -- Clouds -- What comes from clouds? -- Lightning and thunder -- Rainbows -- 6 ways weather is wild -- Wind -- Weather and me -- What in the world?
Keywords: Weather -- Juvenile literature; Weather